Post-Durban climate policy architecture based on linkage of cap-and-trade systems - Matthew Ranson; Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2012)
The outcome of the December 2011 United Nations climate negotiations in Durban, South Africa, provides an important new opportunity to move toward an international climate policy architecture that is capable of delivering broad international participation and significant global CO2 emissions reductions at reasonable cost. We evaluate one important component of potential climate policy architecture for the post-Durban era: links among independent tradable permit systems for greenhouse gases. Because linkage reduces the cost of achieving given targets, there is tremendous pressure to link existing and planned cap-and-trade systems, and in fact, a number of links already or will soon exist. We draw on recent political and economic experience with linkage to evaluate potential roles that linkage may play in post-Durban international climate policy, both in a near-term, de facto architecture of indirect links between regional, national, and sub-national cap-and-trade systems, and in longer-term, more comprehensive bottom-up architecture of direct links. Although linkage will certainly help to reduce long-term abatement costs, it may also serve as an effective mechanism for building institutional and political structure to support a future climate agreement.
Keywords: Q54; Q58; Q40; Q48; 330; Global Climate Change; Market-Based Instruments; Cap-and-Trade; Carbon Pricing; Carbon Taxes; Linkage; International Climate Policy Architecture